Pengembangan Deteksi Suhu dan Kelembaban Laboratorium Elektronika Dengan Menggunakan Metode Fuzzy Logic - Bahrun Niam; Rony Darpono; Martselani Adias Sabara (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
The electronics laboratory is an important place to run the practical activities, especially among electronics students. It is important to protect laboratory equipment and components from the temperature and humidity factors. Whether, the temperature is too cold and the humidity is too high, it caused the corrosion of all electronic components. Thus, it also caused minor until severe damage of the components. Arduino is an open source electronics kit which specially designed to make easier for researcher to develop electronic devices regarding to various sensors and controllers. The laboratory room temperature detection system was carried out by using an Arduino device, which aims to determine the temperature conditions in the laboratory. The method used in this research is the fuzzy logic method. The software used is Arduiono and Matlab, while the hardware is power supply, D1 Mini microcontroller, DHT11 sensor and LCD. The results showed that the temperature data obtained from the DHT11 sensor will be displayed on the LCD. The temperature data obtained is 27 degrees Celsius – 29 degrees Celsius. The system is able to provide information when the temperature and humidity conditions are abnormal and the LED lights up according to room conditions.